Business feasibility study analysis of spontan food & snack tenant at coffee shop samarinda seberang - Surahman Surahman; Rusliansyah Rusliansyah; Nabilah Nabilah; Whil Danugraha (Institute of Computer Science (IOCS), 2025)
The culinary sector in Indonesia is growing rapidly, making the Food & Beverage (F&B) industry one of the most competitive fields in the creative economy. This study aims to assess the feasibility of Spontan Food & Snack, a micro business in Samarinda, using the Business Model Canvas (BMC) approach combined with financial analysis. The method used is a case study with a mixed approach through field observations, interviews, and financial data analysis during one year of operation. The feasibility of the business was analyzed using five main indicators, namely Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Break Even Point (BEP) in units, rupiah, and percentages. The results of the study show that this business is feasible with a positive NPV, an IRR exceeding the discount rate of 9%, and an efficient capital recovery period of four years. The break-even point is reached at sales of 536 units or Rp10,720,000 with a percentage of 41%. Thus, Spontan Food & Snack has good financial prospects and a competitive business model, while emphasizing the importance of integrating financial analysis and BMC in improving operational efficiency and strategic planning for the sustainable development of culinary MSME.